Interpretation of Al-Ahqāf Verse 15 from the Perspective of Zaghlul An-Najjar's Scientific Exegesis: Penafsiran Qs. Al-Ahqāf Ayat 15 Perspektif Tafsir Ilmi Zaghlul An-Najjar - Yenni Rahman; irdaningsih; Ade Setiawan (Ikhtisar: Jurnal Pengetahuan Islam, 2025)
This study analyzes Dr. Zaghlul Raghib An-Najjar’s interpretation of QS. al-Ahqāf [46]:15, particularly the phrase wa waḍa‘at-hu kurhan (وَوَضَعَتْهُ كُرْهًا), which portrays the mother’s suffering during childbirth. The study aims to describe al-Najjar’s scientific exegesis (tafsīr ‘ilmī) methodology. Using a qualitative library-based approach, this research draws from An-Najjar’s Tafsīr al-Āyāt al-Kawniyyah fī al-Qur’ān al-Karīm (2006) and complementary classical and medical literature. The findings reveal that the term kurhan signifies physical, emotional, and spiritual pain aligned with medical understandings of uterine contractions, cervical dilation, and hormonal changes. Al-Najjar’s interpretation demonstrates the harmony between āyāt qauliyyah (divine revelation) and āyāt kauniyyah (natural phenomena), reaffirming that the Qur’an contains timeless scientific truths. In conclusion, his approach presents a balanced integration of theological and empirical dimensions in understanding the Qur’an’s scientific verses.